Perilaku Pengusaha Toko Kelontong Dalam Memilih Pembiayaan Perbankan Syariah Di Kota Mataram - Rizky Raharjo; Taufiq Chaidir; Ihsan Ro’is (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2020)
This study aims to analyze how the behavior of grocery store entrepreneurs in choosing Islamic banking financing. This research uses qualitative methods, data collection was carried out by means of interviews. The informants in this study were Muslim grocery traders who trade in the city of Mataram. The conclusion is that all entrepreneurs need capital for their business. Sociologically, many entrepreneurs follow their relatives around them, namely fellow micro sector entrepreneurs who have already been in contact with Islamic banks so that they choose financing in the same place, then anthropologically, it is seen more broadly that entrepreneurs follow relationships with Islamic banks because of their family and apart from being both businessmen in the micro sector, these relatives are also Muslim, so this is cultured in the environment around him. In addition, the active role of Islamic banking marketing also participates in influencing entrepreneurs to take financing from Islamic banks. Second, its relation to Islamic economic principles. Some entrepreneurs take financing from Islamic banks just because they join in, while other entrepreneurs take financing from Islamic banks because they have knowledge of Islamic economic principles, namely avoiding usury. Grocery store entrepreneurs do not know about the existing products in Islamic banking, the product that is clearly known is the Sharia KUR and grocery store entrepreneurs also know that the product uses a murabahah contract. But on the other hand, quite a lot of entrepreneurs have also interacted with conventional financial institutions, according to entrepreneurs because of an urgent need.